2021
DOI: 10.1038/s41598-021-89587-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the structure and skin permeability of compounds

Abstract: A three-descriptor quantitative structure–activity/toxicity relationship (QSAR/QSTR) model was developed for the skin permeability of a sufficiently large data set consisting of 274 compounds, by applying support vector machine (SVM) together with genetic algorithm. The optimal SVM model possesses the coefficient of determination R2 of 0.946 and root mean square (rms) error of 0.253 for the training set of 139 compounds; and a R2 of 0.872 and rms of 0.302 for the test set of 135 compounds. Compared with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This value is commonly used to quantify the transport of molecules in the epidermal skin’s outermost layer and to highlight the importance of skin absorption. The lesser the log K p value, the lower the cutaneous permeability of the molecule . In this study, compared to ciprofloxacin, the test compounds showed a log K p value (Table ), so these compounds might have better skin permeation than ciprofloxacin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is commonly used to quantify the transport of molecules in the epidermal skin’s outermost layer and to highlight the importance of skin absorption. The lesser the log K p value, the lower the cutaneous permeability of the molecule . In this study, compared to ciprofloxacin, the test compounds showed a log K p value (Table ), so these compounds might have better skin permeation than ciprofloxacin.…”
Section: Resultsmentioning
confidence: 99%
“…The lesser the log K p value, the lower the cutaneous permeability of the molecule. 39 In this study, compared to ciprofloxacin, the test compounds showed a log K p value (Table 4), so these compounds might have better skin permeation than ciprofloxacin. Except for compounds 2, 5, and 6, all of the test compounds and CPFX are predicted to be Pgp substrates.…”
Section: Drug-likeness and Pharmacokinetic Studies Of The Isolated Co...mentioning
confidence: 92%
“…-This descriptor is related to the molecular size and shape of the compounds. 54 The high numerical value of this descriptor makes the compound more toxic, as shown in compounds 135 (octabromodiphenyl ether) (given in Fig. 5) and 165 (tetraethyldithiopyrophosphate) nRCNO (+ve) Number of oximes (aliphatic) Functional group count…”
Section: Number Of Oxygen Atoms Constitutional Descriptormentioning
confidence: 99%
“…As shown in Table 3, the subset of selected peptides displayed lower calculated logP o/w partition coefficients that can be associated with increased permeability across membranes, despite having high molecular weight (>500 Da) and several hydrogen bond interactions. Similarly, different in silico techniques have addressed that the prediction of skin permeability by complex molecules is difficult to achieve; however, those predictions are based on comparisons to experimental data or complex algorithms based on quantitative structure-activity relationships (QSAR) [32,33]. Additonally, the calculated coefficient for binding to serum proteins and skin permeability are in the range of 95% of approved drugs, suggesting a positive interaction with epidermal tissues.…”
Section: Ace Minc Gluc Vegfmentioning
confidence: 99%